2015
DOI: 10.1186/s12933-015-0211-6
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle insulin resistance in salt-sensitive hypertension: role of angiotensin II activation of NFκB

Abstract: BackgroundWe have previously shown that in hypertensive Dahl salt-sensitive (DS) rats, impaired endothelium-dependent relaxation to acetylcholine and to insulin is mechanistically linked to up-regulation of angiotensin (Ang) II actions and the production of reactive oxygen species (ROS) and to activation of the proinflammatory transcription factor (NF)κB. Here we investigated whether Ang II activation of NFκB contributed to insulin resistance in the skeletal muscle of this animal model.MethodsDS rats were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…In 11 maintenance haemodialysis patients, higher muscle sodium content was, in a similar way, associated with insulin resistance [34]. Furthermore, in the soleus muscle of salt-sensitive hypertensive Dahl rats, the RAAS was shown to activate the NF-κB pro-inflammatory pathway, inducing moderate hyperinsulinemia and insulin resistance [33]. A recent study also demonstrated a positive statistical correlation between Na + intake and insulin resistance in obese children and adolescents [35].…”
Section: Na + Homeostasis and Hyperinsulinismmentioning
confidence: 83%
See 1 more Smart Citation
“…In 11 maintenance haemodialysis patients, higher muscle sodium content was, in a similar way, associated with insulin resistance [34]. Furthermore, in the soleus muscle of salt-sensitive hypertensive Dahl rats, the RAAS was shown to activate the NF-κB pro-inflammatory pathway, inducing moderate hyperinsulinemia and insulin resistance [33]. A recent study also demonstrated a positive statistical correlation between Na + intake and insulin resistance in obese children and adolescents [35].…”
Section: Na + Homeostasis and Hyperinsulinismmentioning
confidence: 83%
“…Insulin alone has long been thought to cause Na + retention, with enough effects to contribute to arterial hypertension [32,33]. A study by Brands and colleagues showed that such Na + -retaining effects may be limited to uncontrolled Type II diabetes [32].…”
Section: Na + Homeostasis and Hyperinsulinismmentioning
confidence: 99%
“…Furthermore, it improves the contraction and proliferation of myofibroblasts and promotes the release of inflammatory and pro-fibrotic cytokines, including TGF-β1, and the deposition of extracellular matrix30. The activation of NFκB inflammatory pathway by angiotensin plays also a critical role in insulin resistance of rats subjected to HF31. The deleterious angiotensin-AT1 axis impairs glucose homeostasis and favours insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor plays an important role in cell signal transduction and gene expression regulation, and is also the critical nuclear factor involved in the initiation and regulation of inflammation. In recent years, the inflammatory response mediated by NF-κB is one focus of research into the mechanisms underlying insulin resistance (30,31). Following NF-κB activation, the transcription of inflammatory factors, such as TNF-α, interleukin (IL)-1β and IL-6, is initiated and regulated.…”
Section: Discussionmentioning
confidence: 99%